Chemical constituents and antioxidant capacity of extracts from Elaeis guineensis leaves / Ang Chun Hui - Ang, Chun Hui (2017)
The present study investigated compounds present in Elaeis guineensis leaves and their potentials to act as natural antioxidants. Fresh leaves from Elaeis guineensis fronds were subjected to solvent extraction and ultrasonic-assisted methanol extraction. The chemical constituents were identified by gas chromatography-mass spectrometry (GC-MS). The crude methanolic extract (MeOH) obtained from the ultrasonic-assisted methanol extraction was then fractionated by repeated extractions, sequentially with solvents of different polarity into n-hexane (HEX), ethyl acetate (EA), water (WATER) and insoluble residue (INSOL) fractions. Major compounds identified in the methanolic crude extract which was further partitioned by n-hexane (MeOH-HEX) extract were phytol (42.94%), α-tocopherol (24.97%), squalene (14.95%), β-sitosterol (9.39%) and stigmasterol (5.84%). The same crude methanolic extract treated with activated carbon (MeOH-Activated C) extract yielded 2,4-di-tert-butylphenol (30.88%), phytol (23.80%), methyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (13.49%), 16-heptadecenal (11.72%) and 3,7,11,15-tetramethyl-2-hexadecen-1-ol (7.80%). Maceration using n-hexane as extracting solvent (Maceration-HEX) yielded α-tocopherol (30.51%), squalene (24.23%), arundoin (21.73%), 3-hexen-1-ol (5.31%) and β-sitosterol (4.77%). Maceration using ethyl acetate as extracting solvent (Maceration-Et2O) yielded similar components in slightly different quantities with squalene (29.34%), α-tocopherol (24.35%), phytol (12.54%), arundoin (8.63%) and 3,7,11,15-tetramethyl-2-hexadecen-1-ol (7.42%). The antioxidant activities of the crude methanolic extract and its fractions were evaluated by in vitro 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical-scavenging activity, lipid peroxidation (LPO) inhibition and β-carotene bleaching assays. The total phenolic contents (TPC) in the fractions were determined using Folin-Ciocalteu reagent. The results indicated that the INSOL fraction showed the highest activity in DPPH radical-scavenging activity assay and β-carotene bleaching assay, while the EA fraction exhibited the highest activity through LPO inhibition. DPPH radical-scavenging activities of the fractions were negatively correlated (correlation coefficients = -0.896, -0.943 respectively, P < 0.050) with the TPC based on Pearson Product Moment Correlation and Spearman Rank Order Correlation. The findings of this present study suggests that Elaeis guineensis leaves have a high potential to be utilized as a natural source of antioxidants in palm oil producing countries such as Indonesia, Malaysia and Thailand, where Elaeis guineensis leaves are abundantly available.